Зміни активності NO-синтаз та аргінази у тканині підшлункової залози при введенні L-аргініну або аміногуанідину за умов стрептозотоцин-індукованої гіперглікемії - Панчишин, О.Б.; Панасюк, Н.Б.; Білецька, Л.П.; Скляров, О.Я. (Таврический медико-биологический вестник, 2012)
При стрептозотоцин-индуцированной гипергликемии у крыс изучали влияние L-аргинина и селективного блокатора индуцибельной NO-синтазы аминогунидина на активность NO-синтаз и аргиназы в ткани поджелудочной железы. Показано, что как L-аргинин, так и аминогуанидин снижают активность индуцибельной NO-синтазы, при этом L-аргинин выражено понижает концентрацию глюкозы в крови и повышает активность аргиназы, что свидетельствует об усилении неокислительного пути его метаболизма. The influence of L-arginine and selective inducible NO-synthase blocker aminoguanidine on the activity of NO-synthases and arginase in pancreatic tissue in rats under conditions of streptozotocin-induced hyperglycemia was investigated. It was shown, that both L-arginine and aminoguanidine decrease the activity of inducible NO-synthase, whereas L-arginine supplementation significantly decreases the glucose concentration in blood and increases the activity of arginase, giving evidence about the enhancement of nonoxidative pathway of its metabolism.